Survival impact of surgical resection of primary tumor in patients with stage IV colorectal cancer: Results from a large population‐based cohort study. Issue 5 (12th November 2013) - Ahmed, Shahid; Leis, Anne; Fields, Anthony; Chandra‐Kanthan, Selliah; Haider, Kamal; Alvi, Riaz; Reeder, Bruce; Pahwa, Punam
Abstract : BACKGROUND: Currently, there is very low‐quality evidence available regarding benefit of surgical resection of the primary tumor (SRPT), in patients with stage IV colorectal cancer (CRC). In the absence of randomization, the reported benefit may reflect selection of younger and healthier patients with good performance status. A large population‐based cohort study was undertaken to determine the survival benefit of SRPT in advanced CRC by eliminating various biases reported in the literature. METHODS: A retrospective cohort study involving patients with stage IV CRC, diagnosed between 1992 and 2005, in the province of Saskatchewan, Canada. Survival was estimated by using the Kaplan‐Meier method. Survival distribution was compared by log‐rank test. Cox proportional multivariate regression analysis was performed to determine survival benefit of SRPT by controlling other prognostic variables. RESULTS: A total of 1378 eligible patients were identified. Their median age was 70 years (range, 22‐98 years) and male:female ratio was 1.3:1; 944 (68.5%) of them underwent SRPT. Among 1378 patients, 42.3% received chemotherapy and 19.1% received second‐generation therapy. Patients who underwent SRPT and received chemotherapy had median overall survival of 18.3 months (95% confidence interval [CI] = 16.6‐20 months) compared with 8.4 months (95% CI = 7.1‐9.7 months) if they were treated with chemotherapy alone ( P < .0001). Cox proportional analysis revealed that use of chemotherapy (hazard ratio [HR] = 0.47, 95% CI = 0.41‐0.54), SRPT (HR = 0.49, 95% CI = 0.41‐0.58), second‐line chemotherapy (HR = 0.47, 95% CI = 0.45‐0.64), and metastasectomy (HR = 0.54, 95% CI = 0.45‐0.64) were correlated with superior survival. CONCLUSIONS: SRPT improves survival in patients with stage IV CRC, independent of other prognostic variables including age, performance status, comorbid illness and chemotherapy. Cancer 2014;120:683–691 . © 2013 American Cancer Society . Abstract : Currently, there is very low‐quality evidence available regarding benefit of surgical resection of the primary tumor in patients with stage IV colorectal cancer. This large population‐based cohort study demonstrated that primary tumor resection improves survival of patients with advanced colorectal cancer, independent of other prognostic variables such as age, performance status, comorbid illness, and chemotherapy.